Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 11. Sir William Beveridge, at the outset of his Report (page 8), states that "the plan is based on a diagnosis of want", but the Report does not specify the extent of that want or - what is also important - what it would have cost to abolish it. (35) The Report, however, (pages 7 & 165) refers to certain "Social Surveys made by impartial investigators of living conditions in some of the main industrial centres of Britain between 1938 and 1937" and, in that connection, refers to a Table in Volume III of the "New Survey of London Life & Labour" relative to 1929. From that Table it appears that, in 1929, 11% of all the families in East London were in want; that the average number of persons per family in question was 3.7; and that the average extent to which each of these families fell below the subsistence level adopted by the investigators was 11/- per week. On the basis of those data, and assuming the conditions in East London to be typical of the country as a whole, the cost of abolishing want would, in 1929, have been something in the region of £40 millions a year. (36) Since 1929 Supplementary Old Age Pensions have been instituted in 1940 at a cost of some £30 millions a year. On that point, as stated in the Report (page 91), Mr. Rowntree in his Survey in York in 1936 found that "the poverty due to old age was more acute than that due to any other single cause" and Mr. J.J. Mallon, C.H., Warden of Toynbee Hall, in a letter to the "Times" of 16th December last, in reference to the "Beveridge" Report, made the following statement :- "In estimating the impact of the Beveridge proposals on those who suffer from poverty due to old age, Mr. Rowntree works upon the figures revealed by his inquiry in 1936, but of course since then the supplementary Old Age Pension scheme has come into operation with important consequences. The scale of this scheme as regards aged persons who have no resources is at least as favourable as the Beveridge proposals. Ignoring the slight difference between Mr. Rowntree's poverty line and Sir William's poverty line, it can therefore be said that the position now and the position as it would remain, even should the Beveridge proposals not be adopted, is that as regards persons entitled to Old Age Pensions under the present arrangements, there is no reason whatever why any of them should be in a state of poverty as Mr. Rowntree defines that state". It is also relevant to note that, of those drawing Old Age Pensions today [- averaging some 9/6d per week -] some two-thirds (i.e. some 2 millions) do not in fact draw the Supplementary Pensions to which they would be entitled/ 200/B/3/2/C216/5/50